The right to refuse unwanted citations: rethinking the culture of science around the citation - Jaime A. Teixeira da Silva (Scientometrics, 2021)
Logically, and by most common standards, academics would be pleased to be cited, considering it a form of recognition of their intellect. In return, especially those with high citation counts, such as Clarivate Analytics’ Highly Cited Researchers, can benefit through peer recognition, rewards, funding, securing a better position, or expanding a collaborative network. Despite known and untold benefits, one issue has not been discussed: the right to refuse to be cited or the right to refuse a citation. Academics might not want to be cited by papers published in truly predatory journals, papers with false authors, or sting papers with falsified elements that employ underhanded ethical tactics. Currently, academics generally have the freedom to select where they publish their findings and choose studies they cite, so it is highly probable that requests to remove citations or refuse citations might never become formal publishing policy. Nonetheless, this academic discussion is worth having as valid and invalid literature increasingly gets mixed through citations, and as the grey zone between predatory/non-predatory and scholarly/unscholarly becomes increasingly difficult to distinguish.